Treatise on Medicine from the Funds of the Bakhchisaray Museum-Reserve - Abibullayeva E.E. (Золотоордынское обозрение)
Objective: To acquaint the domestic and foreign academic audience with the written source on medicine from the period of the Crimean Khanate, by providing its basic information (essence, content, style). Research materials: Original handwritten Arabic-language text of a medical treatise from the funds of the Bakhchisarai Historical, Cultural and Archaeological Museum-Reserve; data from the Kadiasker notebook for the year 1674–1675 from the Republican Crimean Tatar Library named after I. Gasprinsky. Research results and novelty: In the course of the work on a collection of books from the funds of the Bakhchisaray Museum-Reserve, a treatise on medicine was identified and studied. The materials presented below can significantly enrich the existing knowledge about the little-studied aspect of history, such as the medicine and practical methods of treatment in everyday life in the Crimean Khanate. Transliteration and translation into Russian of the fragments of the text will help the researchers to form a picture of diseases, practices and methods of healing and recovery through both individual medicinal plants and recipes.